Morphemes, spelling and development: Comments on "The timing and mechanisms of children's use of morphological information in spelling" by S. Pacton and H. Deacon - Bryant, P; Nunes, T (2008)
In our comments on Pacton and Deacon's discussion of children's spelling of morphemes we raise four issues: (1) whether the "timing" question should be about children's ages or about their psychological processes; (2) the crucial importance of individual differences in the study of the connections that people make between morphemes and spelling; (3) the conclusions that can be drawn from evidence for the use of non-morphemic spelling strategies; (4) the need to consider the results of intervention studies in any account of children's understanding and use of morphemic spelling rules. © 2007.